2017
DOI: 10.1080/10717544.2017.1365393
|View full text |Cite
|
Sign up to set email alerts
|

Redox-responsive PEGylated self-assembled prodrug-nanoparticles formed by single disulfide bond bridge periplocymarin-vitamin E conjugate for liver cancer chemotherapy

Abstract: Periplocymarin (PPM), a cardiac glycoside, has a narrow therapeutic index, poor tumor selectivity and severe cardiovascular toxicity which hinder its wide clinical applications in cancer treatment. Herein, we report novel redox-responsive prodrug-nanoparticles (MPSSV-NPs) self-assembled by co-nanoprecipitation of PPM-vitamin E conjugate and a PEG derivative of linoleate (mPEG2000-LA) in water. It was found that the characteristics of PPM-vitamin E nanoparticles (PSSV-NPs) were improved through co-nanoprecipita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Ginger extractive (10% gingerol) was purchased from Nanjing Zelang Biological Technology Co. Ltd. (Nanjing, China). mPEG 2K -LA was synthesized in our laboratory [32]. (3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and trypsin were provided by the Beyotime Institute of Biotechnology (Jiangsu, China).…”
Section: Methodsmentioning
confidence: 99%
“…Ginger extractive (10% gingerol) was purchased from Nanjing Zelang Biological Technology Co. Ltd. (Nanjing, China). mPEG 2K -LA was synthesized in our laboratory [32]. (3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and trypsin were provided by the Beyotime Institute of Biotechnology (Jiangsu, China).…”
Section: Methodsmentioning
confidence: 99%
“…In the last few decades, redox-responsive drug delivery systems have been designed to target cancers specifically and keep the high therapeutic concentration while reduce side effects (Li et al, 2020). Especially, the disulfide bond-based conjugate has been received increasing attention recently (Li et al, 2018;Sun et al, 2018;Zhang et al, 2017), which is stable in the blood and normal tissues (low reductive conditions) (Yang, Sun, et al, 2020). Compared to normal cells, the tumor cells overproduce the glutathione (GSH), which could cause the rapid destruction of the disulfide bond to achieve stimuli-responsiveness (Du et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Periplocymarin (PPM) is isolated from cortex periplocae, the dry root of Periploca sepium Bge, which is traditionally used as antirheumatic and diuretic agent in Chinese medicine (7). Previous studies have indicated that, PPM performed antitumor effects in various of cancer (8,9). For example, it has been found that PPM promoted prostate adenocarcinoma (PC3) cell apoptosis and inhibit proliferation of U937, HCT-8, Bel-7402, BGC823, A549, and A2780 cell lines in vitro with IC50 values of 0.02-0.29 mM (10).…”
Section: Introductionmentioning
confidence: 99%